2021
DOI: 10.1017/s0007114521003561
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of the Dietary Approaches to Stop Hypertension diet provides novel insights for the nutritional epidemiology of type 2 diabetes mellitus

Abstract: Adherence to the DASH diet is inversely associated with T2DM risk. Metabolic changes due to DASH adherence and their potential relationship with incident T2DM have not been described. The objective is to determine metabolite clusters associated with adherence to a DASH-like diet in the Insulin Resistance Atherosclerosis Study (IRAS) cohort and explore if the clusters predicted 5-year incidence of T2DM. The current study included the 570 non-diabetic multi-ethnic participants aged 40 - 69 years. Adherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Fourth, two main components, nuts and sodium, were not assessed in our study. This may change the metabolite clusters in the DASH pattern in our study and may affect the physiological mechanism of T2DM prevention ( 41 ) . For the PCA-derived prudent pattern in our study, a high intake of healthy foods like in the Mediterranean diet including fish, vegetables and legumes, along with a high intake of unhealthy foods such as meat may invalidate the benefits of the former.…”
Section: Discussionmentioning
confidence: 93%
“…Fourth, two main components, nuts and sodium, were not assessed in our study. This may change the metabolite clusters in the DASH pattern in our study and may affect the physiological mechanism of T2DM prevention ( 41 ) . For the PCA-derived prudent pattern in our study, a high intake of healthy foods like in the Mediterranean diet including fish, vegetables and legumes, along with a high intake of unhealthy foods such as meat may invalidate the benefits of the former.…”
Section: Discussionmentioning
confidence: 93%
“…The energy-restricted dietary regimens such as the Mediterranean diet, the Dietary Approaches to Stop Hypertension (DASH) diet, the plant-based diets were reported to ameliorate insulin sensitivity and reduce the incidence of T2D ( 166 ). In particular, in a post-hoc analysis of the Insulin Resistance Atherosclerosis Study cohort, an inverse association between the adherence to the DASH diet and the risk of T2D has been reported ( 167 ). Similar results were documented for MS; in this case, the adherence to the DASH diet was associated with a 64% lower risk to develop MS in healthy children and adolescents ( 168 ).…”
Section: Improvement Of the Vitamin D-based Strategies In CV Preventionmentioning
confidence: 99%
“…To date, the most rigorous investigations that identified DASH-related metabolomic markers were studies utilizing data from randomized controlled feeding studies, including the DASH trial [ 12 ] and DASH Mechanism Study [ 26 ]. Several observational studies also identified circulating metabolomic markers for DASH dietary patterns in general populations, including the Cancer Prevention Study (CPS)-II Nutrition Cohort among postmenopausal women [ 27 ], the Framingham Offspring Study [ 28 ], the Atherosclerosis Risk in Communities Study (ARIC) [ 29 ], the Chronic Renal Insufficiency Cohort (CRIC) study [ 30 ], and the Insulin Resistance Atherosclerosis Study (IRAS) [ 31 ]. Although most DASH-related metabolites are lipids and lipid-like molecules, among these studies conducted with general populations, only a few metabolites were replicated.…”
Section: Discussionmentioning
confidence: 99%